From Silence to Strength: Leveraging CTCA and Gbeleyi 1.0 to Tackle Gender Dynamics and Student Anxiety in Secondary Schools - Gbeleyi, Olasunkanmi; Owoyemi, Saheed; Peters, Esther; agb, Deborah; Ebinson, Aderonke; Adeleye, Jeremiah (Journal of Educational Sciences, 2025)
Anxiety and critical thinking skills are crucial factors influencing students' academic performance and learning outcomes, particularly in subjects perceived as difficult. This study attempted find out the relative effectiveness of CTCA, Gbeleyi 1.0 and the lecture method on students’ anxiety, and critical thinking skills to logic gate. A mixed-method design was adopted for data collection. The study population comprises of 213 (JS) two students who at the time of the study had not taken the (BECE) to ascertain the level of potency of the methods in question. The selected schools were randomly selected, 131 and 81 males. A pretest and posttest consisting of the anxiety test, and the critical thinking skill task were administered to the groups. The Critical Thinking Skill Task (CTST), Students’ Anxiety Scale Test (SAST) and Students’ Interview Guide (SIG) were the instruments developed for this study. A respectable reliability coefficient of 0.78 and 0.74 was obtained from the respectively. Data collection took six weeks, and the analysis was conducted using IBM SPSS version 23. The collected data underwent multivariate analysis of covariance. The results revealed a significant difference in the methods used, univariate ANOVA on anxiety [F (3, 209) = 13.38; p<0.05]. However, gender does not have a statistically significant effect (F = 0.842, p = .360), nor does the interaction between method and gender (F = 2.262, p = .134), suggesting that the impact of methods on post-anxiety does not vary significantly by gender.